1992
DOI: 10.1128/jvi.66.6.3347-3354.1992
|View full text |Cite
|
Sign up to set email alerts
|

Simian virus 40 T antigen activates the late promoter by modulating the activity of negative regulatory elements

Abstract: Late promoter activity measured before viral DNA replication results from a complex involvement of negative and positive cis-acting elements located both in the enhancer and in the 21-bp repeats. GC motifs located within the 21-bp repeats act in cooperation with sequences overlapping the early TATA box to down-regulate the late promoter activity. Analysis of insertion mutants indicates that the late promoter might be negatively regulated at least partially by the early promoter machinery. The GTI motif located… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1994
1994
2000
2000

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…Similarly, transcriptional activation by T antigen of the SV40 early and late promoters in vitro occurs efficiently with preparations of T antigen unable to specifically bind DNA (14). However, analysis of the late promoter has indicated that the T-antigen binding sites at the origin of replication contribute to activation (7,27,36). In addition, several mutations within T antigen that inhibit its DNA-binding activity resulted in lower levels of activation, also suggesting a role for DNA-binding activity in transactivation (6,26,60).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, transcriptional activation by T antigen of the SV40 early and late promoters in vitro occurs efficiently with preparations of T antigen unable to specifically bind DNA (14). However, analysis of the late promoter has indicated that the T-antigen binding sites at the origin of replication contribute to activation (7,27,36). In addition, several mutations within T antigen that inhibit its DNA-binding activity resulted in lower levels of activation, also suggesting a role for DNA-binding activity in transactivation (6,26,60).…”
Section: Discussionmentioning
confidence: 99%
“…T antigen interacts directly with both TEF-1 and TBP, and induction of the late promoter is abolished with T-antigen fragments that fail to bind either of these factors, with a single exception (22). Although TEF-1 binding sites are clearly necessary for induction of the late promoter, other sequences have been identified that also contribute to activation (7,17,18,27,36,47). These include sequences in the enhancer and 21-bp repeats, as well as sequences at the origin of DNA replication.…”
mentioning
confidence: 99%